2002
DOI: 10.1097/01.lab.0000022225.45996.21
|View full text |Cite
|
Sign up to set email alerts
|

Association of Spasmolytic Polypeptide–Expressing Metaplasia with Carcinogen Administration and Oxyntic Atrophy in Rats

Abstract: SUMMARY:Spasmolytic polypeptide (TFF2)-expressing metaplasia (SPEM) is a gastric metaplastic lineage associated with the development of intestinal-type gastric adenocarcinoma. To study the etiology of this potential neoplastic precursor metaplasia, we used surgical rat models of remnant gastric adenocarcinoma studied with and without exposure to nitroso carcinogen. Animals with truncal vagotomy without duodenogastric reflux procedures demonstrated normal mucous neck cell spasmolytic polypeptide (SP) immunostai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
2
17
2
Order By: Relevance
“…Large gland cells expressing both TFF2 and IF in different subcellular compartments are typical for spasmolytic polypeptide-expressing metaplasia. 43 Here, in fundic polyps, TFF2 expression levels were comparable with those normally found in fundic neck cells and overlapping with the pattern of GS-lectin/Muc6 staining. The size of TFF2 expressing cells was the same 2 in a wild-type mouse).…”
Section: Fundic Polyp Glands Distinct From Spasmolytic Polypeptide Exmentioning
confidence: 53%
“…Large gland cells expressing both TFF2 and IF in different subcellular compartments are typical for spasmolytic polypeptide-expressing metaplasia. 43 Here, in fundic polyps, TFF2 expression levels were comparable with those normally found in fundic neck cells and overlapping with the pattern of GS-lectin/Muc6 staining. The size of TFF2 expressing cells was the same 2 in a wild-type mouse).…”
Section: Fundic Polyp Glands Distinct From Spasmolytic Polypeptide Exmentioning
confidence: 53%
“…In previous studies, we have reported that SPEM is observed in the gastric mucosa adjacent to human gastric cancer. 20,21 SPEM was also observed at the base of fundic glands showing oxyntic atrophy in rodent models such as Helicobacter felis-infected mice, 14 rats with remnant gastric cancer 16 and mice treated with DMP-777. 17 DMP-777 is a cell-permeant neutrophil elastase inhibitor that depletes parietal cells by acting as a secretory membrane protonophore.…”
mentioning
confidence: 96%
“…11 Since the parietal cell plays a critical role in the differentiation of gastric mucosal lineages, 12,13 the loss of parietal cells is associated with a number of lineage changes, including foveolar hyperplasia, loss of chief cells and mucous cell metaplasia. [14][15][16][17] The normal gastric mucosa includes two types of mucous cells: surface mucous cells secrete trefoil factor family 1 (TFF1) and mucin M1 (MUC5AC), whereas mucous neck cells secrete spasmolytic polypeptide/trefoil factor 2 (SP/ TFF2) and MUC6. A number of investigations in rodents have shown that loss of gastric parietal cells leads to the evolution of SP-expressing metaplasia (SPEM), a gastric fundic metaplastic lineage with TFF2-expressing mucous cells with Brunner's gland or deep antral gland morphology.…”
mentioning
confidence: 99%
“…Since some SPEM cells have been found to coexpress TFF2 and intrinsic factor (IF), 11 a specific secretory product of mouse chief cells, we examined whether IF was also expressed in the expanded fundic mucous cell compartment of the GÀ/À mice. Using double-fluorescent labeling with GSII and rabbit-a-IF, we found little overlap of GSII-positive cells with IF-positive cells in either WT (Figure 4c) or GÀ/À mice (Figure 4d).…”
Section: Fundic Gland Mucous Cells In Gà/à Mice Do Not Express Chief mentioning
confidence: 99%
“…6 Emergence of a prominent mucous cell lineage (the so-called 'mucous cell metaplasia') was found to be one of the earliest histological changes in the fundic mucosa of these mice. 5 Mucosal changes bearing similar features have also been reported in a variety of pathological processes in human and mouse, which include H. pylori infection; [7][8][9] loss of parietal cells upon chemical administration; 10 treatment with a carcinogen, 11 mutation of the Kcnq1 gene encoding a potassium channel, 12 and constitutively active STAT3. 13 This type of mucosal change may therefore represent a common, and possibly reversible 10 response of the stomach, to mucosal injury and tissue inflammation triggered by various stimuli.…”
mentioning
confidence: 99%